Biotransformations in organic chemistry : a textbook - Faber, K. (Kurt), 1953- (Berlin ; Heidelberg : Springer-Verlag, 2011)
This, the sixth edition of the established textbook on biocatalysis, feeds into undergraduate and graduate courses in modern organic chemistry, as well being a concise introduction to the field. New material includes colour graphics and cutting-edge research
1 Introduction and Background Information 1.1 Introduction... 1.2 Common Prejudices Against Enzymes... 1.3 Advantages and Disadvantages of Biocatalysts... 1.3.1 Advantages of Biocatalysts... 1.3.2 Disadvantages of Biocatalysts... 1.3.3 Isolated Enzymes Versus Whole Cell Systems... 1.4 Enzyme Properties and Nomenclature... 1.4.1 Structural Biology in a Nutshell... 1.4.2 Mechanistic Aspects of Enzyme Catalysis... 1.4.3 Classification and Nomenclature... 1.4.4 Coenzymes... 1.4.5 Enzyme Sources... References... ... 2 Biocatalytic Applications 2.1 Hydrolytic Reactions... 2.1.1 Mechanistic and Kinetic Aspects... 2.1.2 Hydrolysis of the Amide Bond... 2.1.3 Ester Hydrolysis... 2.1.3.1 Esterases and Proteases... 2.1.3.2 Lipases... 2.1.4 Hydrolysis and Formation of Phosphate Esters... 2.1.5 Hydrolysis of Epoxides... 2.1.6 Hydrolysis of Nitriles... References... 2.2 Reduction Reactions... 2.2.1 Recycling of Cofactors... 2.2.2 Reduction of Aldehydes and Ketones Using Isolated Enzymes... 2.2.3 Reduction of Aldehydes and Ketones Using Whole Cells... 2.2.4 Reduction of C=C-Bonds ... References... 2.3 Oxidation Reactions... 2.3.1 Oxidation of Alcohols and Aldehydes... 2.3.2 Oxygenation Reactions... 2.3.2.1 Hydroxylation of Alkanes... 2.3.2.2 Hydroxylation of Aromatic Compounds... 2.3.2.3 Epoxidation of Alkenes... 2.3.2.4 Sulfoxidation Reactions... 2.3.2.5 Baeyer-Villiger Reactions... 2.3.2.6 Formation of Peroxides... 2.3.2.7 Dihydroxylation of Aromatic Compounds... 2.3.3 Peroxidation Reactions... References... ... 2.4 Formation of Carbon-Carbon Bonds... 2.4.1 Aldol Reactions... 2.4.2 Thiamine-Dependent Acyloin- and Benzoin Reactions... 2.4.3 Michael-Type Additions... References... 2.5 Addition and Elimination Reactions... 2.5.1 Cyanohydrin Formation... 2.5.2 Addition of Water... 2.5.3 Addition of Ammonia... References... 2.6 Transfer Reactions... 2.6.1 Glycosyl Transfer Transferases... 2.6.1.1 Glycosyl Transferases... 2.6.1.2 Glycosidases... 2.6.2 Amino Transfer Reactions... References... 2.7 Halogenation and Dehalogenation Reactions... 2.7.1 Halogenation... 2.7.2 Dehalogenation... References... 3 Special Techniques 3.1 Enzymes in Organic Solvents... 3.1.1 Ester Synthesis... 3.1.2 Lactone Synthesis... 3.1.3 Amide Synthesis... 3.1.4 Peptide Synthesis... 3.1.5 Peracid Synthesis... 3.1.6 Redox Reactions... 3.1.7 Medium Engineering... 3.2 Immobilization... 3.3 Artificial and Modified Enzymes... 3.3.1 Artificial Enzyme Mimics... 3.3.2 Modified Enzymes... 3.3.2.1 Chemically Modified Enzymes... 3.3.2.2 Genetically Modified Enzymes... 3.3.3 Catalytic Antibodies... References... 4 State of the Art and Outlook... 5 Appendix 5.1 Basic Rules for Handling Biocatalysts... 5.2 Abbreviations... 5.3 Suppliers of Enzymes... 5.4 Commonly Used Enzyme Preparations... 5.5 Major Culture Collections... 5.6 Pathogenic Bacteria and Fungi...
Includes bibliographical references and index.
Keywords: Enzymes -- Biotechnology; Biotransformation (Metabolism); Organic compounds -- Synthesis